Metrological support of gamma-ray measurements in Ukraine - Yatsyshyn, Svyatoslav; Lazarenko, Sergii; Lazarenko, Nadiya (Видавництво Львівської політехніки, 2020)
The specific of metrological support for different types of dosemeters are considered. Gamma-ray sensors are commonly used for measuring radiation doses as also the fluid levels in the industry. Typically, the 60Co or 137Cs isotopes as the radiation source are applied. For instance, in the USA, such detectors are beginning to be used as part of the Container Security Initiative [1]. Problems of their metrological assurance are becoming more general. They require the development of metrological support. There are conducted researches of calibration, metrological verification, and determination of the sensitivity of gammaray dosemeters, based on the joint application of installations equipped with ionizing radiation sources and of X-ray installations. The implementation of the Program of Integration of Ukraine into the European Union requires harmonization of Ukrainian and International standards, in the field of metrological assurance of means for measuring the characteristics of ionizing radiation including. Recently, several regulatory, methodological documents and issues have been published. They concern the dosimetric measurement of gamma-ray characteristics in the field of radiation safety, diagnostics, and therapy.
Keywords: Dosemeters; Reference equipment; Ionizing radiation; Calibration; Metrological assurance; Spectrum